The Appreciation and Study of Qur’an Manuscripts from Southeast Asia: Past, Present, and Future - Annabel Teh Gallop (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2015)
The focus of this paper is not on theological aspects of the Qur’an, or on the study of the Qur’anic sciences in Southeast Asia over the past centuries, but rather to attempt to trace the path of the appreciation of old copies of the Qur’an in Southeast Asia as part of the historical record of the Islamic heritage of the region.  In this light, Qur’an manuscripts are viewed as objects of material culture which can cast light on the societies which produced them, and as works of art which testify to the heights of artistic creativity in the region, for illuminated Qur’an manuscripts represent the pinnacle of achievements in the arts of the book in Southeast Asia. This historical record can be measured through a survey of how, where, when and by whom Qur’an manuscripts in Southeast Asia were collected, documented, studied and published, both in Southeast Asia itself and in the west.